Major depressive disorder in chronic heart failure patients: Does silent cerebral infarction cause major depressive disorder in this patient population? - Güliz Kozdağ; İrem Yaluğ; Nagihan İnan; Gökhan Ertaş; Macit Selekler; Hüseyin Kutlu; Ayşe Kutlu; Ender Emre; Metin Çetin; Dilek Ural (KARE Publishing, 2015)
OBJECTIVE: Depression frequently occurs in patients with heart failure as similar pathophysiological mechanisms present in both these diseases. Patients with dilated cardiomyopathy (DCM) have a high incidence of clinically asymptomatic silent cerebral infarction (SCI). This study aimed to evaluate the relation between SCI and major depressive disorder (MDD), and between MDD and clinical and biochemical parameters in DCM patients. METHODS: Patients with ischemic and non-ischemic DCM who had chronic heart failure (CHF) (39 male, 10 female, age 60+-10 years) were included in the study. Mean patient ejection fraction (EF) was 34+-10%. Patients had no localized neurological symptoms or stroke history. The etiology of DCM was ischemic in 40 and non-ischemic in 9 patients. Twentyfive age-matched healthy volunteers served as a control group for comparison of SCI and MDD prevalence. RESULTS: Patients had mild to severe CHF symptoms. Prevalence of SCI and MDD was significantly higher in patients with DCM than in the control group; 63% vs 8%; p<0.001, and 52% vs 20%; p<0.001 respectively. Patients with SCI had a higher prevalence of MDD than patients without SCI in DCM (61% vs 27%, p=0.02). CONCLUSION: CHF patients have an increased prevalence of SCI and MDD. Patients with SCI have a higher prevalence of MDD compared to patients without SCI in CHF.